Interactive electrical behaviour in mormyrid weakly electric fish: jamming avoidance response or social interaction? - Nils Weimar; Moritz Maxeiner; Emily M. Wong; Ingolf P. Rick; Mathis Hocke; Tim Landgraf; Gerhard von der Emde (Animal Behaviour, 2025)

Future climate projections in the global coastal ocean - Jason Holt; Anna Katavouta; Joanne Hopkins; Laurent O. Amoudry; Christian M. Appendini; Lars Arneborg; Alex Arnold; Yuri Artioli; Jerome Aucan; Barbara Berx; Laura Cagigal; Michela De Dominicis; et al. (Progress in Oceanography, 2025)

twoPhaseInterTrackFoam: An OpenFOAM module for arbitrary Lagrangian/Eulerian interface tracking with surfactants and subgrid-scale modeling - Moritz Schwarzmeier; Suraj Raju; Željko Tuković; Mathis Fricke; Dieter Bothe; Tomislav Marić (Computer Physics Communications, 2025)

Interactive effects of multiple stressors in coastal ecosystems - Shubham Krishna; Carsten Lemmen; Serra Örey; Jennifer Rehren; Julien Di Pane; Moritz Mathis; Miriam Püts; Sascha Hokamp; Himansu Kesari Pradhan; Matthias Hasenbein; Jürgen Scheffran; Kai W. Wirtz (Frontiers in Marine Science, 2025)
Coastal ecosystems are increasingly experiencing anthropogenic pressures such as climate warming, CO 2 increase, metal and organic pollution, overfishing, and resource extraction. Some resulting stressors are more direct like pollution and fisheries, and others more indirect like ocean acidification, yet they jointly affect marine biota, communities, and entire ecosystems. While single-stressor effects have been widely investigated, the interactive effects of multiple stressors on ecosystems are less researched. In this study, we review the literature on multiple stressors and their interactive effects in coastal environments across organisms. We classify the interactions into three categories: synergistic, additive, and antagonistic. We found phytoplankton and bivalves to be the most studied taxonomic groups. Climate warming is identified as the most dominant stressor which, in combination, with other stressors such as ocean acidification, eutrophication, and metal pollution exacerbate adverse effects on physiological traits such as growth rate, fitness, basal respiration, and size. Phytoplankton appears to be most sensitive to interactions between warming, metal and nutrient pollution. In warm and nutrient-enriched environments, the presence of metals considerably affects the uptake of nutrients, and increases respiration costs and toxin production in phytoplankton. For bivalves, warming and low pH are the most lethal stressors. The combined effect of heat stress and ocean acidification leads to decreased growth rate, shell size, and acid-base regulation capacity in bivalves. However, for a holistic understanding of how coastal food webs will evolve with ongoing changes, we suggest more research on ecosystem-level responses. This can be achieved by combining in-situ observations from controlled environments (e.g. mesocosm experiments) with modelling approaches.

Tidal impacts on air-sea CO2 exchange on the North-West European shelf - Jan Kossack; Moritz Mathis; Ute Daewel; Feifei Liu; Kubilay Timur Demir; Helmuth Thomas; Corinna Schrum (Frontiers in Marine Science, 2024)
Tidal forcing is a dominant physical forcing mechanism on the Northwest European Shelf (NWES) that regulates the mixing-stratification status of the water column and thus acts as a major control for biological productivity and air-sea CO 2 exchange. Tides further influence the marine carbon cycle on the shelf by affecting benthic-pelagic coupling, vertical mixing and the large-scale residual circulation. The cumulative tidal impact on oceanic uptake of atmospheric CO 2 on the NWES, however, remains largely unexplored. We use a coupled physical-biogeochemical ocean model to gain quantitative understanding of the tidal impacts on the air-sea CO 2 exchange of the NWES by comparing hindcast simulations with and without tidal forcing. Our results show that tidal forcing weakens the annual oceanic CO 2 uptake on the NWES by 0.15 T m o l C y r − 1 , corresponding to a ~13% stronger CO 2 sink in the experiment without tidal forcing. The tide-induced increase in marine primary production demonstrated in earlier studies, which primarily enhances biological carbon fixation in shallow inner-shelf regions of the NWES, does not significantly affect net air-sea CO 2 exchange. Instead, we find tidal mixing, tide-induced baroclinic circulation and the tidal impact on benthic-pelagic coupling to be dominant controls of air-sea CO 2 exchange. Tidal mixing in the permanently mixed shelf regions accounts for the majority (~40%) of the weakening effect on CO 2 uptake, while the modulation of water mass composition in the Celtic Sea by tide-induced baroclinic circulation reduces the uptake further (~33% of the difference in annual mean CO 2 uptake). In terms of the shelf carbon budget, the tidal response of air-sea CO 2 exchange is primarily mediated by changes to the pelagic DIC reservoir (~73%; − 0.11 T m o l C y r − 1 ). Tidal impacts on off-shelf carbon export to the North Atlantic only account for ~20% ( − 0.03 T m o l C y r − 1 ) of the tidal impact on shelf CO 2 uptake, and changes in sedimentation of particulate organic carbon account for the remaining ~7% ( − 0.01 T m o l C y r − 1 ) .

Adding to the mix – Challenges of mixed‐fisheries management in the North Sea under climate change and technical interactions - Bernhard Kühn; Alexander Kempf; Thomas Brunel; Harriet Cole; Moritz Mathis; Klaas Sys; Vanessa Trijoulet; Youen Vermard; Marc Taylor (Fisheries Management and Ecology, 2023)
Technical interactions (multiple fleets fishing multiple species with various gears, as either target or bycatch), bycatch regulations through a landing obligation, and biological and economic effects of climate change, affecting fisheries yield and profits, provide a challenge for demersal mixed fisheries of the North Sea. A multi‐stock, multi‐fleet, bioeconomic model was used to understand management options under these combined influences. Scenarios considered climate change effects on recruitment of three main gadoid stocks (cod – Gadus morhua , saithe – Pollachius virens , whiting – Merlangius merlangus ), possible future developments of fuel and fish prices, and strict implementation of a landing obligation. The latter leads to decreased yield and profits in the short term due to increased choke effects, mainly of North Sea cod, being influenced by climate‐induced productivity changes. Allowing fishing above F MSY , but within sustainable limits, or limiting year‐to‐year quota changes, could help buffer initial losses at the expense of decreased profits in the mid‐ to long‐term. Economic performance of individual fleets was linked to their main target's stock status, cost structure, and fuel and fish prices. The results highlight a need to consider both biological and economic consequences of climate change in the management of mixed fisheries.

Barotropic and baroclinic tides increase primary production on the Northwest European Shelf - Jan Kossack; Moritz Mathis; Ute Daewel; Yinglong Joseph Zhang; Corinna Schrum (Frontiers in Marine Science, 2023)
High biological productivity and the efficient export of carbon-enriched subsurface waters to the open ocean via the continental shelf pump mechanism make mid-latitude continental shelves like the northwest European shelf (NWES) significant sinks for atmospheric CO 2 . Tidal forcing, as one of the regionally dominant physical forcing mechanisms, regulates the mixing-stratification status of the water column that acts as a major control for biological productivity on the NWES. Because of the complexity of the shelf system and the spatial heterogeneity of tidal impacts, there still are large knowledge gaps on the role of tides for the magnitude and variability of biological carbon fixation on the NWES. In our study, we utilize the flexible cross-scale modeling capabilities of the novel coupled hydrodynamic–biogeochemical modeling system SCHISM–ECOSMO to quantify the tidal impacts on primary production on the NWES. We assess the impact of both the barotropic tide and the kilometrical-scale internal tide field explicitly resolved in this study by comparing simulated hindcasts with and without tidal forcing. Our results suggest that tidal forcing increases biological productivity on the NWES and that around 16% (14.47 Mt C) of annual mean primary production on the shelf is related to tidal forcing. Vertical mixing of nutrients by the barotropic tide particularly invigorates primary production in tidal frontal regions, whereas resuspension and mixing of particulate organic matter by tides locally hinders primary production in shallow permanently mixed regions. The tidal impact on primary production is generally low in deep central and outer shelf areas except for the southwestern Celtic Sea, where tidal forcing substantially increases annual mean primary production by 25% (1.53 Mt C). Tide-generated vertical mixing of nutrients across the pycnocline, largely attributed to the internal tide field, explains one-fifth of the tidal response of summer NPP in the southwestern Celtic Sea. Our results therefore suggest that the tidal NPP response in the southwestern Celtic Sea is caused by a combination of processes likely including tide-induced lateral on-shelf transport of nutrients. The tidally enhanced turbulent mixing of nutrients fuels new production in the seasonally stratified parts of the NWES, which may impact the air–sea CO 2 exchange on the shelf.

Historical increases in land‐derived nutrient inputs may alleviate effects of a changing physical climate on the oceanic carbon cycle - Fabrice Lacroix; Tatiana Ilyina; Moritz Mathis; Goulven G. Laruelle; Pierre Regnier (Global Change Biology, 2021)
The implications of climate change and other human perturbations on the oceanic carbon cycle are still associated with large uncertainties. Global‐scale modelling studies are essential to investigate anthropogenic perturbations of oceanic carbon fluxes but, until now, they have not considered the impacts of temporal changes in riverine and atmospheric inputs of P and N on the marine net biological productivity (NPP) and air–sea CO 2 exchange (FCO 2 ). To address this, we perform a series of simulations using an enhanced version of the global ocean biogeochemistry model HAMOCC to isolate effects arising from (1) increasing atmospheric CO 2 levels, (2) a changing physical climate and (3) alterations in inputs of terrigenous P and N on marine carbon cycling over the 1905–2010 period. Our simulations reveal that our first‐order approximation of increased terrigenous nutrient inputs causes an enhancement of 2.15 Pg C year −1 of the global marine NPP, a relative increase of +5% over the simulation period. This increase completely compensates the simulated NPP decrease as a result of increased upper ocean stratification of −3% in relative terms. The coastal ocean undergoes a global relative increase of 14% in NPP arising largely from increased riverine inputs, with regional increases exceeding 100%, for instance on the shelves of the Bay of Bengal. The imprint of enhanced terrigenous nutrient inputs is also simulated further offshore, inducing a 1.75 Pg C year −1 (+4%) enhancement of the NPP in the open ocean. This finding implies that the perturbation of carbon fluxes through coastal eutrophication may extend further offshore than that was previously assumed. While increased nutrient inputs are the largest driver of change for the CO 2 uptake at the regional scale and enhance the global coastal ocean CO 2 uptake by 0.02 Pg C year −1 , they only marginally affect the FCO 2 of the open ocean over our study's timeline.

Possible impacts of anthropogenic climate change to the upwelling in the South Brazil Bight - Mihael Machado de Souza; Moritz Mathis; Bernhard Mayer; Maurício Almeida Noernberg; Thomas Pohlmann (Climate Dynamics, 2020)
Anthropogenic climate change is expected to strengthen upwelling events worldwide, driven by an increase of upwelling-favorable winds. However, Earth System Models (ESM) tend to underestimate regional processes due to their coarse grid resolution, which can lead to local biases. We use a high-resolution ocean model ( $${1/12}^{° }$$ 1 / 12 ∘ ) forced by results from the Max-Planck-Institute-ESM to analyze the impact of the RCP8.5 emission scenario on the upwelling of South Atlantic Central Water (SACW) in the South Brazil Bight (SBB). We find a stronger Ekman forcing and a higher spread of SACW over the shelf, but this does not translate into higher vertical velocities at the bottom of the mixed-layer in the end of the century. The increased winds’ effect is essentially balanced by an increase in water column stability due to the surface warming. This is particularly important during austral summer, when this process tends to weaken the upwelling. Vertical velocities decrease significantly along the shelf break. Here, the upwelling regime is governed by the Brazil Current (BC) and slight changes in transport induce large responses in upwelling strength. The consequences are increased sea surface temperatures over most of the shelf, although mitigated by the SACW upwelling and kept below global projections. However, temperatures decrease along Cabo Frio. In this region, shelf break upwelling dominates and is enhanced by a local increase in the BC transport. This highlights the importance of regional processes and, more specifically, of changes in the BC transport for the upwelling in the SBB.

The impact of meltwater discharge from the Greenland ice sheet on the Atlantic nutrient supply to the northwest European shelf - Moritz Mathis; Uwe Mikolajewicz (Ocean Science, 2020)
Projected future shoaling of the wintertime mixed layer in the northeast (NE) Atlantic has been shown to induce a regime shift in the main nutrient supply pathway from the Atlantic to the northwest European shelf (NWES) near the end of the 21st century. While reduced winter convection leads to a substantial decrease in the vertical nutrient supply and biological productivity in the open ocean, vertical mixing processes at the shelf break maintain a connection to the subpycnocline nutrient pool and thus productivity on the shelf. Here, we investigate how meltwater discharge from the Greenland ice sheet (GIS), not yet taken into account, impacts the mixed layer shoaling and the regime shift in terms of spatial distribution and temporal variability. To this end, we have downscaled sensitivity experiments by a global Earth system model for various GIS melting rates with a regionally coupled ocean–atmosphere climate system model. The model results indicate that increasing GIS meltwater discharge leads to a general intensification of the regime shift. Atlantic subpycnocline water masses mixed up at the shelf break become richer in nutrients and thus further limit the projected nutrient decline on the shelf. Moreover, the stronger vertical nutrient gradient through the pycnocline results in an enhanced interannual variability of on-shelf nutrient fluxes which, however, do not significantly increase variations in nutrient concentrations and primary production on the shelf. Due to the impact of the GIS meltwater discharge on the NE Atlantic mixed layer depth, the regime shift becomes initiated earlier in the century. The effect on the onset timing, though, is found to be strongly damped by the weakening of the Atlantic meridional overturning circulation. A GIS melting rate that is even 10 times higher than expected for emission scenario Representative Concentration Pathway (RCP) 8.5 would not lead to an onset of the regime shift until the 2070s.

Driving mechanisms of the variability and long-term trend of the Brazil–Malvinas confluence during the 21st century - Mihael M. de Souza; Moritz Mathis; Thomas Pohlmann (Climate Dynamics, 2019)

Which complexity of regional climate system models is essential for downscaling anthropogenic climate change in the Northwest European Shelf? - Moritz Mathis; Alberto Elizalde; Uwe Mikolajewicz (Climate Dynamics, 2018)